Static Indoor Object Detection Using MATLAB For Visually Impaired - Shaha, Pritam; Kshatriya, Niranjan; Borse, Rahul (International Journal of Computer Sciences and Engineering, 2025)
Detection of indoor static objects by visually impaired without help of third person is a crucial task. The indoor object detection enables a visually impaired to settle on suitable and convenient choices of route to follow in an indoor area. Literature presents that methods such as Electronic Travel Aids (ETA), Augmented Reality (AR) and Navigation Assistance for Visually Impaired (NAVI) are used to assist visually impaired. These methods are expensive and involves overhead for every decision. This paper presents an algorithmic based model which uses machine learning technique. In the proposed methodology firstly, the database is prepared which consist of various images of objects to train the system. During the use, the image which is captured by the visually impaired is compared with entries of the database to detect the object. The experiments were conducted using MATLAB for image recognition and analysis.